2015
DOI: 10.1002/2014ja020301
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering local magnetospheric processes governing the morphology and variability of Ganymede's aurora using three‐dimensional multifluid simulations of Ganymede's magnetosphere

Abstract: We investigate local magnetospheric processes governing the morphology and variability of Ganymede's aurora depending on its position with respect to the center of the Jovian plasma sheet. We couple an existing three-dimensional multifluid simulation to a new aurora brightness model developed for this study. With this, we are able to qualitatively and quantitatively show that the short-and long-period variabilities observed in Ganymede's auroral footprint at Jupiter are also predicted to be present in the brig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 23 publications
6
15
0
Order By: Relevance
“…Both bands, particularly the ion band, approximately agree with in situ measurements by HST, reproduced in the bottom panel of Figure . They are also consistent with Figure 4 of Payan et al () from multi‐ion MHD simulations with a more realistic brightness model, particularly the case where the moon is near the center of the Jovian plasma sheet, which is consistent with our simulation setup (flyby G8).…”
Section: Simulation Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Both bands, particularly the ion band, approximately agree with in situ measurements by HST, reproduced in the bottom panel of Figure . They are also consistent with Figure 4 of Payan et al () from multi‐ion MHD simulations with a more realistic brightness model, particularly the case where the moon is near the center of the Jovian plasma sheet, which is consistent with our simulation setup (flyby G8).…”
Section: Simulation Resultssupporting
confidence: 92%
“…Paty et al used multi‐ion MHD model to study how different ion species are supplied at the ionosphere and convected and energized in the magnetosphere (Paty & Winglee, , ; Paty et al, ). They further developed a brightness model to understand the morphology of Ganymede's auroral oval (Payan et al, ). Later, Dorelli et al () showed that introduction of Hall effect in an MHD model produced significant asymmetry in plasma flow paths and modified the local field line topology.…”
Section: Introductionmentioning
confidence: 99%
“…In the cusp, energetic (∼keV) precipitating ions were observed, and plasma flows became strongly field‐aligned, flowing downward into the surface of the moon. The location of the cusp crossing is consistent with both multifluid simulations by Payan et al () and observations by the Hubble Space Telescope by McGrath et al ().…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with passage through the cusp, just prior to entering the polar cap, ion flow velocities shifted to become highly field aligned, flowing down toward the surface of the moon, and the energy spectrogram shows signs of energized (∼ keV) precipitating ions. The location of this proposed cusp crossing ( 18.723.7 latitude, 149.2137.8 longitude, G‐Phi‐Omega) is consistent with the of Ganymede's auroral oval in both three‐dimensional multifluid simulations by Payan et al () and observations by the Hubble Space Telescope (McGrath et al, ).…”
Section: Galileo Pls Observations During the G01 Flybysupporting
confidence: 85%
“…The observations of the auroral ovals as observed in the UV might also be used to characterize the subsurface ocean (Saur et al 2015). Numerous modeling studies have showed that electron impact is the dominant dissociation mechanism of O 2 (Saur et al 1998;Eviatar et al 2001;Payan et al 2015), leading to the generation of atomic oxygen in the O( Observations of emissions in the visible are also good parameters for determining the different energetic inputs coming in upper planetary atmospheres, i.e. solar UV photons and precipitating particles, with the green (557.7 nm) and reddoublet (630, 636.4 nm) lines coming from the deactivation of oxygen atoms in the O( 1 S) and O( 1 D) states, respectively.…”
Section: Introduction and Motivationsmentioning
confidence: 99%